Intrinsic motivation, digital enablement and brand relationship quality: investigation in higher education - Urooj, Ahmed; Rukhsar, Ahmed; Sharizal, Hashim; Mahani, Mohammad Abdu Shakur (Emerald Publishing Ltd, 2025)
Purpose This study examines the impact of intrinsic motivation elements – job autonomy, competence and relatedness – on employee–brand relationship quality (EBRQ) in higher education institutions (HEIs), focusing on the moderating role of digital enablement within the context of digital sustainability.